Standards Process of Learning Implementation in SMP Harapan Ibu Banyuasin, Indonesia - Amanda, Rizqi Dian; Lian, Bukman; Putra, Alhadi Yan (Journal of Social Work and Science Education, 2022)
This study aimed at determining how does the standard process in English Learning at SMP Harapan Ibu Tanah Mas Banyuasin. This study was a qualitative using study case method. This study was done at SMP Harapan Ibu Tanah Mas Banyuasin with six respondents were the headmaster, assistant of the headmaster in curriculum, operator, administration staff, and two teachers of English. Data collection technique used in this study were interview, observation and documenting. The truthworthness in this study was using triangulation. The findings showed that (1) the implementation of standard process at SMP Harapan Ibu has done according to the national standart at the school which they still used the school based urriculum and curriculum of 2013; (2) the learning implementation has conveyed aaccording to the schedule of the school; (3) findings the differences implementation of using school based curriculum has been conveying in 7 and 8-1 class, and using curriculum of 2013 at 8-2, 9-1 and 9-2 class.